1999
DOI: 10.2527/1999.772291x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of implants on daily gains of steers wintered on dormant native tallgrass prairie, subsequent performance, and carcass characteristics.

Abstract: Fall-weaned crossbred steer calves (n = 300; 184 +/- 2.9 kg) received either no implant (Control) or were implanted with Synovex-C (SC = 10 mg estradiol benzoate + 100 mg progesterone), Synovex-S (SS = 20 mg estradiol benzoate + 200 mg progesterone), or Revalor-G (RG = 8 mg estradiol-17beta + 40 mg trenbolone acetate) to determine the effects of implants on weight gain during winter grazing on dormant tallgrass prairie, subsequent grazing and finishing performance, and carcass characteristics. Steers grazed tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…Roeber et al (2000) found skeletal maturities similar to nonimplanted controls when the initial combination implant was administered at 59 d after the beginning of the trial compared with implanting at 0 d, which advanced skeletal maturities by 11 or 16 points. Paisley et al (1999) evaluated the effect of various estrogenic implants (i.e., Synovex-C, Synovex-S [Zoetis, Florham Park, NJ], or Revalor-G [Merck Animal Health, Summitt, NJ]) in steers during wintering period on skeletal maturity. The steers were harvested at about 22 mo of age and skeletal maturity was advanced by 20 to 24% with the use of estrogenic implants during the wintering phase.…”
Section: Effects On Skeletal Maturity Marbling and Tendernessmentioning
confidence: 99%
“…Roeber et al (2000) found skeletal maturities similar to nonimplanted controls when the initial combination implant was administered at 59 d after the beginning of the trial compared with implanting at 0 d, which advanced skeletal maturities by 11 or 16 points. Paisley et al (1999) evaluated the effect of various estrogenic implants (i.e., Synovex-C, Synovex-S [Zoetis, Florham Park, NJ], or Revalor-G [Merck Animal Health, Summitt, NJ]) in steers during wintering period on skeletal maturity. The steers were harvested at about 22 mo of age and skeletal maturity was advanced by 20 to 24% with the use of estrogenic implants during the wintering phase.…”
Section: Effects On Skeletal Maturity Marbling and Tendernessmentioning
confidence: 99%
“…Nowadays, some preparations on the market show faster oestradiol release (Daxenberger et al, 2000), and other recent studies investigated higher dosages and shorter withdrawal periods. There were at least six publications in The Journal of Animal Science alone during 1999, that recommend repeated or multiple treatments of different combined preparations to achieve optimal growth promotion and nutrient retention (Duckett et al, 1999;Holzer et al, 1999;Paisley et al, 1999;Rumsey et al, 1999a,b;Smith et al, 1999). Such information is also available from the internet (NebGuide, 1997), but pharmacokinetic data have not been elaborated in any of these studies and published residue data from real-world treatments were not available.…”
Section: Data On Residues In Meat and Meat Products At The Retail Levmentioning
confidence: 99%
“…The comparison of healthy prepubertal children with Turner syndrome girls highlights the important role of low oestrogen concentrations in childhood. In healthy, prepubertal girls transient signs of pseudo-precocious puberty were associated with accidental intake of oestrogens (Pasquino et al, 1982). The concentrations of oestrogens that regulate growth and development during childhood are very low, but possible effects of dietary oestrogens on such low concentrations are unclear.…”
Section: Possible Role Of Low Doses Of Sex Steroidsmentioning
confidence: 99%
“…The manufacturers' instructions provided with the preparations, for instance, do not contain any explicit warning against multiple application. Even in the scientific literature, repeated or multiple treatment of different combined preparations is often recommended to achieve optimal results (4)(5)(6)(7)(8)(9).…”
mentioning
confidence: 99%